Pelatihan Penerapan Imunostimulan dan Probiotik Pada Budidaya Udang Vaname (Litopenaeus Vannamei) Untuk Meningkatkan Hasil Panen Petambak di Desa Pajurangan, Gending, Probolinggo - Gunanti Mahasri; Rahayu Kusdarwati; Boedi Setya Rahardja; W. Angan Indrawan; Alanosi Noor Muhammad; Farizka Vinka Trinendyah; Faisol Mas’ud; Endah Sih Prihatini; Fuquh Rahmat Shaleh (Universitas Islam Lamongan, 2024)
Probolinggo Regency has a very large fisheries sector potential consisting of the capture fisheries subsector, the aquaculture subsector (ponds, ponds and cages) and the fisheries processing subsector which has the potential to be developed, with total production in the aquaculture sector of 8,084,060 kg/Ha. One of the commodities that is widely cultivated in ponds in Probolinggo Regency is vaname shrimp, both in monoculture and polyculture, with total production in 2017 for vaname shrimp amounting to 2,100.50 tons. Most of the shrimp cultivation production is obtained from intensive pond cultivation which covers an area of 500 hectares and this pond area contributes 90 percent of the total shrimp production in Probolinggo Regency. Problems that have long occurred among shrimp farmers in ponds include: 1) Low knowledge of cultivation technology, 2) Failure to harvest, if possible the harvest has not been able to meet the target and is experiencing a decline, 3) Shrimp that are kept are easily attacked by disease and 4) decline water quality during maintenance. The aim of this community service is to increase the yield of vaname shrimp for a group of beginner farmers, Pajurangan Village, Gending District, Probolinggo Regency. The solution applied to solve this problem is the application of immunostimulants from Zoothamnium sp protein. for the purpose of increasing the shrimp's body defenses and using probiotic EM-4 to improve and maintain water quality and help the absorption of food essences in the shrimp' body. To achieve this goal, the implementation of this community service activity consists of three stages, namely: (a) the socialization stage of cultivation methods with immunostimulants and probiotics, (b) the immunization and probiotic propagation training stage and (c) the application stage of cultivation methods with immunostimulants and probiotics in the pond.